Commentary on "Alignment Between Children's Numeracy Performance, the Kindergarten Common Core State Standards for Mathematics, and State-Level Early Learning Standards" - Karen C. Fuson; Douglas H. Clements; Julie Sarama (SAGE Publishing, 2021)
Litkowski et al. compare preschoolers' performance on three counting items to various standards. We clarify that the items Litkowski and colleagues found to be too easy for kindergarten were actually goals for 4s/PKs in the National Research Council's report Mathematics Learning in Early Childhood: Paths Toward Excellence and Equity but that they were included as kindergarten standards to ensure that all children had an opportunity to learn these crucial competencies. The helpful analysis in their article of the variability across present state early childhood standards indicates that the kindergarten Common Core State Standards-Mathematics need to remain unchanged for the same reason. We suggest that research funding in early childhood is better spent on research on high-quality instructional contexts for all children than on survey research. And we address the important question of what more-advanced children should learn in kindergarten by pairing standards those children already know with crucial standards that need a lot of time and attention.